An Archaeological Survey of Lassen Volcanic National Park, California - Journey, Alfred E. (the Digital Archaeological Record)
This study reports on a survey of the areas in Lassen Volcanic National Park most likely to reveal aboriginal human activity, with some work in the areas less likely to have sites. Despite the limitations, the survey includes virtually every major drainage, meadow, spring, lake, pond, and rock shelter. It represents a large sample of the total park area which would be suitable for human use. In total, forty-seven archaeological sites were located and described. Therefore, this report represents a substantial piece of work in the area of prehistoric human utilization of Lassen Volcanic National Park.